Penggunaan Eyelash Extension Ditinjau dari Hukum Islam - Khasana, Zahratul; Elfanni, Thera Zifatra; Candrika, Gita; Saputri, Vionda Gita; Fitri, Rahma (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This research aims to contribute to the Islamic treasures regarding the prohibition of changing Allah's creation and add to campus literature regarding the Islamic perspective on eyelash extensions. This research is qualitative library research with the object of study being library data in the form of books, literature, notes and relevant reports. The approach used in this research is a historical approach that can be used to understand religion in an empirical setting or formal form that applies in society. The results of this research are as follows: First, eyelash extension, also known as eyelash implantation, is a procedure for attaching false eyelashes to real eyelashes to make them look long, thick and curly, with the aim of beautifying oneself. Second, the views of Salaf scholars and Khalaf scholars regarding the law of attaching false hair which can be linked to eyelash extensions. Third, the use of eyelash extensions is prohibited in Islamic law, because it falls into the category of changing Allah's creation which in jurisprudence is made qiyas by connecting hair.